1969
DOI: 10.1002/app.1969.070130607
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced emulsion polymerization of vinyl acetate and styrene

Abstract: SynopsisStudies have been made of the 7-induced emulsion polymerization of styrene and comparisons made with chemically initiated emulsion polymerization. The polymerization proceeded smoothly to high conversions at 0 and 60°C, the reaction showing a high G (monomer) value. Complete conversions were obtained with total doses of less than 0.05 Mrad. In accordance with the behavior expected of systems having a constant rate of initiation, the molecular weight was found to decrease with decreasing temperature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Stannett 94 reported an order of dependence of 0.79 at 30°C over a similar range of γ dose rates to that used in this work.…”
Section: Dependence Of Polymerization Rates On Temperature and Gamma supporting
confidence: 62%
See 2 more Smart Citations
“…Stannett 94 reported an order of dependence of 0.79 at 30°C over a similar range of γ dose rates to that used in this work.…”
Section: Dependence Of Polymerization Rates On Temperature and Gamma supporting
confidence: 62%
“…The other references to post-irradiation behaviour only mention whether or not there was significant post irradiation polymerization 93,94 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the dependence of the rate of polymerization on ionic strength, based on the fact that the dependence of adsorption rate of the charged polymeric radicals to the already existing polymer particle on ionic strength, approaches first order when ionic strength is below 0.01. 26…”
Section: Resultsmentioning
confidence: 99%
“…The low power dependence DP on the concentrations of emulsifier and initiator was attributed to the frequent chain transfer to monomer, followed by the large desorption of oligomeric radical from the polymer particle due to high water solubility of the monomer. 26…”
Section: Resultsmentioning
confidence: 99%